Hand hygiene by the nursing team in home care: a cross-sectional study - Jéssica Fernanda Corrêa Cordeiro; Mayra Gonçalves Menegueti; Ana Maria Laus; Anaclara Ferreira Veiga Tipple; Rodrigo Carvalho Santana; Silvia Rita Marin da Silva Canini (SciELO, 2021)
ABSTRACT Objective: to identify whether nursing professionals carry out hand hygiene, how they do it, and what resources are available for this practice during home visits. Method: cross-sectional study conducted in a public Home Care service. The World Health Organization instrument was used to observe the hand hygiene technique, the time of performance, and the product used. Results: a total of 940 hand hygiene opportunities taking place in 231 home visits were observed. Overall adherence was 14.4%, with the practice of hand hygiene being higher after contact with the patient (53.7%). Before aseptic procedures, after risk/exposure to body fluids, after contact with the patient's environment, and before contact with the patient, adherence was 0.4%. Regarding the quality of the technique, in none of the 135 practices the recommended steps were followed. As for the structure available in the households, 35 (15.2%) had accessible sinks and none had liquid soap and alcohol-based formulation. Conclusion: adherence to hand hygiene by nursing professionals in home care was low, the technique was not performed, and households did not have resources for the practice.